Ground-penetrating radar investigation of regolith thickness on a periglacial alpine summit flat, Uinta Mountains, Utah, USA - Jeffrey S. Munroe (Arctic, Antarctic, and Alpine Research)
Summit flats are low-relief, gently sloping landforms common in periglacial mountain environments. Apart from at their edges where summit flats are truncated by glacial headwalls and at their crests where isolated tors are occasionally present, bedrock is typically mantled on a summit flat by a continuous layer of regolith. This study applied ground-penetrating radar (GPR) to survey the thickness of regolith on a summit flat in the Uinta Mountains (Utah, USA). More than 500 m of GPR data were collected along transects extending from the edge of the summit flat to the crest, as well as adjacent to a deep soil pit. Results indicate that the regolith thickness is quite variable, with a mean of 91 ± 38 cm when calculated with an appropriate radar velocity. Because the ground surface of the summit flat is notably smooth, the variability in thickness is a consequence of irregularities in the bedrock surface at depth, which is significantly rougher. Recognition that regolith thickness can vary considerably beneath an alpine summit flat has implications for soil formation, carbon storage, and the transmission and storage of shallow groundwater, as well as evolutionary models for periglacial mountain landscapes.